Game as a Motivating Tool in Teaching a Foreign Language - D.Djoldasbaeva (Genius Journals, 2022)
The given article deals with motivating tool in teaching language as – a game. There are given educational material, including games, for practicing and consolidating pronunciation skills, vocabulary, grammatical skills. Also, there are means and techniques which activate the learners’ mental activity, make the learning process effective and at the same time attractive and interesting
Keywords: game; motivation; foreign language; techniques